A Painter in the City: Valery Kondakov - Sirina, Anna (project baikal, 2014)
This article is about activity of Valery Kondakov, Siberian artist and writer, who lives on the shore of Lake Baikal. In search for his own identity he uses the Neo-Archaic style, while emphasizing the importance of ethno-cultural heritage. However, the regional/territorial identity and freedom are more important for the artist than simple ethnicity.